Climate and land use interactively affect lake phytoplankton nutrient limitation status. Issue 2 (1st February 2015) - Hayes, Nicole M.; Vanni, Michael J.; Horgan, Martin J.; Renwick, William H.
Abstract : Climate‐change models predict more frequent and intense summer droughts for many areas, including the midwestern United States. Precipitation quantity and intensity in turn drive the rates and ratios at which nitrogen (N) and phosphorus (P) are exported from watersheds into lakes, but these rates and ratios are also modulated by watershed land use. This led us to ask the question, is the effect of precipitation on phytoplankton nutrient limitation dependent on watershed land use? Across 42 lakes, we found that phytoplankton in lakes in agricultural landscapes were usually P limited but shifted to strong N limitation under increased drought intensity, and that droughts promoted N‐fixing cyanobacteria. In contrast, phytoplankton in lakes with forested watersheds were consistently N limited, regardless of drought status. This climate–land use interaction suggests that droughts may increase the incidence of N limitation in agriculturally impacted lakes. N limitation would likely impair valuable ecosystem services such as drinking water, fisheries, and recreation by promoting the occurrence and severity of cyanobacterial blooms.